KECANGGIHAN TEKNOLOGI INFORMASI DAN KINERJA INDIVIDU DI BANK PERKREDITAN RAKYAT - Cindy Lestari, Ni Kadek Ayu; Juliarsa, Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023DO - 10.24843/EEB.2023.v12.i10.p13, 2023)
Information technology sophistication consists of 4 dimensions that can affect individual performance. The study aims to determine the effect of information technology sophistication in terms of technological sophistication, informational sophistication, functional sophistication, and managerial sophistication on individual performance at Rural Banks (BPR) in Denpasar City. The research population was all AIS users at Rural Banks in Denpasar City. The sample was determined by nonprobability sampling method and purposive sampling technique with the criteria of Rural Banks listed on the website www.ojk.go.id and willing to be sampled. Respondents were obtained as many as 52 people with the criteria of director, accounting employee, credit employee, and customer service or teller/cashier. Data analysis techniques using Statistical Program for Social Science (SPSS) with descriptive statistical tests and inferential statistics tests. The results of the analysis show that technological sophistication, informational sophistication, functional sophistication, and managerial sophistication have a positive and significant effect on individual performance.